Available treatment options for hyperuricemic patients - Mihai-Emil Gherghina; Ileana Peride; Mirela Tiglis; Tiberiu Paul Neagu; Andrei Niculae; Ionel Alexandru Checherita (Romanian Journal of Medical Practice, 2021)
The negative impact of an elevated serum uric acid on the onset and/or progression of different diseases is well known. During the last decade, new forms of therapies were developed, with beneficial results on correcting hyperuricemia, but also with potential side effects that should not be overlooked as most of the hyperuricemic patients are presenting concomitant comorbidities that could influence the decision in prescribing a specific lowering serum uric acid drug. The review will describe recent treatment options, part of them available also in our country.